Gender demographics in urology in Europe: trend analysis over a 10-year period - Sierra, Alba; Pagés, Rita; Sinha, Mriganka; Juliebø-Jones, Patrick; Bosschieter, Judith; Rassweiler-Seyfried, Marie-Claire; Xavier Keller, Etienne; Panthier, Frederic; De Coninck, Vincent; Esperto, Francesco; Hunziker, Manuela; Beisland, Christian; et al. (European urology focus, 2025)
Background and objective - We analysed gender trends for urology trainees and consultants across nine European countries (Spain, UK, Netherlands, Norway, Germany, France, Belgium, Italy, and Switzerland) over a 10-yr period (2012-2022) to gain insight into gender dynamics in urology and determine if there is increasing representation of women in the profession. This information will help in the development of more effective strategies to promote gender equality. - Methods - Data from the past decade were collected, encompassing trainee and consultant records nationally. The project focused on gender demographics within the field of urology, looking at trends in the nine countries. Information was obtained from national registries and supplemented with additional data sources where necessary. - Key findings and limitations - Our results reveal significant variations in gender composition of urology trainees, displaying a slight increase in the presence of female trainees across most countries. This trend was particularly remarkable in Spain and Belgium where the proportion of female urologists exceeded 50%, indicating a potential generational shift within the field. Furthermore, among consultants, there was a global annual increase of 6.7% in female representation, with notable rises in the UK, France, Swiss and Belgium. These trends were also reflected in the membership affiliation data of the European Association of Urology during the same timeframe. - Conclusions and clinical implications - The observed growth in female trainees and consultants offers valuable insights for educational and workforce planning. It is important to understand the evolving dynamics in the field of urology, especially for trainee demographics. Furthermore, the potential engagement of this with more countries could provide a comprehensive view of urology trends across Europe and worldwide. - Patient summary - We looked at the proportion of urology trainees and consultants who are women across Europe. We found that overall, the percentage of females in these roles increased from 2012 to 2022, especially for urology trainees, but there are differences by country. Even if these trends continue, it will take many years before there is equal representation of men and women doctors in urology.